A study to understand the role of social media marketing in an international industrial organisation, and the advantages and disadvantages of using this strategy in the organisation. - Ramesh, Deepika (2012)
It is unquestionable that the internet has made a huge impact on the society as a whole. Social media is one such advanced technology tool that has become the latest trends in people’s lives. The success of social media can be seen in terms of the million Facebook, Twitter and LinkedIn users. Hence, many companies have started using the various social media platform as a marketing tool in order to capitalise on the benefits of using this tool. This paper hopes to understand the role of social media marketing in an industrial B2B organisation, and also to gain a better understanding of the advantages and disadvantages of using this marketing strategy in the organisation. Despite the lack of research in this field, the literature review presented in this study hopes to give a better understanding of the research problem to the audience of this paper. For the purpose of this study an international organisation in the technology industry, was considered as case study for the analysis. Eight key members of the organisation in different geographical locations were interviewed to gain valuable information for the research. The findings from this research provide evidence that social media marketing is an effective marketing strategy and that the advantages of using this marketing strategy over-shadows the disadvantages in terms of building relationships with clients, strengthening brand awareness and employer branding. Finally, this dissertation paper concludes with recommendations for future research in this field. Keywords: Social Media, Social media marketing, Industrial organisation.